Overtraining: "Rusko's rules"
The Finnish researcher Heikki Rusko has developed another way to check for overtraining, and the new technique is very easy to carry out. After working closely with elite Finnish cross country skiers, some of whom became over-trained during 13 weeks of intensified training, Rusko developed a simple 'orthostatic test' which can often foretell the troubling condition. To perform Rusko's test, you simply lie quietly for 10 minutes at the same time every day while monitoring your heart rate, which should stay constant during the 10-minute period.